Strategic Communication and Political Candidate's Image in Digital Campaigns - Gatut Priyowidodo; Inri Inggrit Indrayani (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2024)
This research aims to present a comprehensive bibliometric literature evaluation related to research topics that have relevance to political candidate image building during 2000-2023 and the future research of political candidate image building. Data materials were obtained from Google Scholar by filtering 303 articles from 994 data that were successfully recompiled. Data downloading was carried out on January 10th, 2023. The research method was bibliometric. Data was downloaded through the PoP (Publish or Perish) version 8 application. For future research, topics related to globalization, Twitter, blogs, and rhetoric have opportunities to be developed in contemporary political communication studies.